A Influência da identidade projetada na reputação organizacional - Ana Luisa de Castro Almeida (2005)
This research evaluated the impacts of the projected identity on reputation in the internal and external publics' perception, recognizing that a better understanding of this social process can contribute for the organizations to work on their relationships with the stakeholders. This study was the first in Brazil to analyze the relationship between projected identity and reputation, concepts consolidated in the academic centers in Europe and United States, and it adopted measurement techniques applied in international studies such as the Reputation Quotient (RQ);Perceived External Prestige (PEP), Projected Identity (APOI), Organizational Identification Degree (OID) and Organizational Citizenship Behavior (OCB). Reputation has become one of the intangible assets of great value for the organizations in the relationship with theirenvironment, and its creation and maintenance have become a challenge that needs to be dealt with over the years. Thus, one can perceive a larger investment and professionalization of the communication processes aiming at projecting the organizations in the public space in conditionsthat assure them distinctiveness and attractiveness. The communication helps the organizations build the idea of " who we are " and their publics build the idea of "how they see the organizations", establishing the relationship between identity and reputation. This research wascarried together with the publics of the Dom Cabral Foundation, Brazilian institution for executive development. We have analyzed how the company presents itself and how adherent the internal and external publics are to what is projected. Soon after, we have researched the perception of the eternal public's reputation. Aggregating to those studies, we have also analyzed the impact of the projected identity and perceived external prestige on the internal public's identification and citizenship behavior. The results of the qualitative and quantitative approachesindicated significant relationships among perceived external prestige, agreement with projected attributes, organizational identification and organizational citizenship behavior. We can affirm that the better the employees' perception about the external prestige of the organization, the better the agreement degree with what it projects about itself and the better their identification. In other words, the better the alignment between the organizational speech and the internal perception, thebetter the relationships established between organization and employees will be. The exception is the variable attractiveness of the attributes which, in the method of linear regression, has notshown itself as significant in the relationship with identification and with the organizational citizenship behavior. In other words, there are no evidences saying that the attributes have to be attractive, but they need indeed to be practiced by the organization. The empirical analysis ofFDC's reputation aligns itself with the theoretical studies, showing not only the existent relationship between projected identity and reputation, but how the sense building about symbolic aspects of its reputation are sustained in the perceptions of divulged attributes. We highlight thatthe organizational competence to create, maintain and sustain a positive reputation can represent the consolidation of a competitive advantage, differentiated, non-imitable, of significant and maintainable value over the years. We hope this research contributes with the studies on themesthat impact strongly the sustainability of the businesses.